OTA based current-mode sinusoidal quadrature oscillator with non-interactive control - Summart, Saksit; Thongsopa, Chanchai; Jaikla, Winai (My University, 2012)
The current-mode quadrature oscillator with non-Interactive 2 current control for both of condition of oscillation (CO) and frequency of oscillation (FO) using 4 operational transconductance amplifiers (OTAs) and 2 grounded capacitors Is presented. The proposed oscillator provides 2 sinusoidal output currents with 90° phase difference. It also provides high output impedances that make the circuit can directly drive load without additional current buffers. The condition of oscillation and the frequency of oscillation can be electronically/independently controlled by adjusting the bias current of the OTA. The use of only grounded capacitors without any external resistor is ideal for integration.
Keywords: Current-mode; Non-interactive control; OTA; Quadrature oscillator